Sesquiterpenes and alkaloids from Scorodocarpus borneensis - Wiart, Christophe; Martin, Marie-Thérèse; Awang, Khalijah; Hue, Nathalie; Serani, Laurent; Laprévote, Olivier; Paı̈s, Mary; Rhamani, Mawardi (Elsevier, 2001)
A new sesquiterpene, scodopin, and a mixture of three tryptamine-type alkaloids, scorodocarpines A-C, were isolated from the fruits of Scorodocarpus borneensis, together with a known hemisynthetic sesquiterpene, cadalene-β-carboxylic acid, which was isolated from the bark. The structures of the new compounds were elucidated by interpretation of spectral data, especially tandem mass spectrometry for the alkaloid mixture.